Epinephrine Compound: Unveiling Its Optical and Thermochemical Properties via Quantum Computation Methods - Kareem, Rebaz Obaid; Kebiroğlu, Mehmet Hanifi; Hamad, Othman Abdulrahman; Kaygili, Omer; Bulut, Niyazi (Iranian Chemical Science and Technologies Association, 2023)
This study employs Density Functional Theory (DFT) methodology to comprehensively investigate the structural and physicochemical characteristics of epinephrine, a molecule of physiological relevance. By employing DFT approaches, a more precise description of epinephrine's structure and properties is achieved compared to prior studies. A detailed examination of epinephrine's structure and various properties, such as the Highest Occupied Molecular Orbital (HOMO), Lowest Unoccupied Molecular Orbital (LUMO), Band Gap (BG), Density of States (DOS), Fourier-Transform Infrared Spectroscopy (FT-IR), Ultraviolet (UV) absorption, and Natural Bond Orbital (NBO) analysis. Furthermore, we explore non-covalent interactions (NCI) through the examination of Reduced Density Gradient (RDG) and Molecular Electrostatic Potential (MEP) maps. Incorporating FT-IR results, we delve into the vibrational properties of epinephrine, highlighting C-H vibrations at 3700, 3176.20, and 2986.14 cm-1, along with specific vibrational modes of the benzene ring at 1558.43 and 1461.14 cm-1. Additionally, we provide a comprehensive analysis of epinephrine's thermochemical properties at temperatures ranging from 100 to 200 K under constant pressure conditions (1 atm), including optical transitions. This comprehensive investigation enhances our understanding of epinephrine's structure and properties, paving the way for a more profound comprehension of its biological and pharmacological significance. © 2023, Iranian Chemical Science and Technologies Association. All rights reserved.
Keywords: Epinephrine; NCI; Optical properties; Physicochemical; RDG; thermochemistry